2006
DOI: 10.1109/tps.2006.872174
|View full text |Cite
|
Sign up to set email alerts
|

Molar ratio and energy efficiency of DeNO/sub x/ using an intermittent DBD ammonia radical injection system

Abstract: Ammonia radicals are produced by a dielectric barrier discharge (DBD) in a chamber, called radical injector, which is separate from the chamber that NO gas flows. The radicals are injected into the mixing zone in NO gas flow field to decompose NO gas. The power source for generating the DBD is a one cycle sinusoidal (OCS) waveform so as to easily control the electrical power consumed in the DBD plasma. The fundamental frequency of the OCS power source is 150 kHz. Based on the molar ratio of ammonia particles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…With decreasing removal ratio (less than 80%), the energy efficiency of fast polarity reversal becomes higher than that of slower polarity reversal. Recently, Yukimura and colleagues reported that energy efficiency values above 100 g/kWh could be obtained by ammonia radical injection into a plasma [15]. So far as we know, however, no one has reported successful NO removal with a high energy efficiency (over 60 g/kWh) by plasma without any additives, Fig.…”
Section: Influence Of Voltage Rise Timementioning
confidence: 99%
“…With decreasing removal ratio (less than 80%), the energy efficiency of fast polarity reversal becomes higher than that of slower polarity reversal. Recently, Yukimura and colleagues reported that energy efficiency values above 100 g/kWh could be obtained by ammonia radical injection into a plasma [15]. So far as we know, however, no one has reported successful NO removal with a high energy efficiency (over 60 g/kWh) by plasma without any additives, Fig.…”
Section: Influence Of Voltage Rise Timementioning
confidence: 99%
“…NH3, water vapor and hydrogen peroxide (H2O2) vapor are commonly used as radical source in many researches. It was reported [10][11] that radical injection could reduce energy consumption and improve energy efficiency in the removal of NOx by plasma with NH3 injection. When NH3 is used as an additive for DeNOx process, the final byproducts are stable, and are easily collected in the form of powders such as NH4NO3 [12].…”
Section: Introductionmentioning
confidence: 99%
“…NOx must be removed because it leads to the formation of acid rain and photochemical smog and it is related to several adverse effects on human health, mainly in heart and lungs. Nonthermal plasma is proposed as a prominent non-conventional technique, which can simultaneously treat several pollutants at atmospheric pressure; furthermore, the initial investment and operation costs are relatively low [2].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and modeling researches focus on the discharge phenomena and reaction kinetics during the plasma remediation of NOx using dielectric barrier discharges (DBDs) [2]. In reality, DBD is a modified corona discharge and the characteristic of a DBD device is the presence of a dielectric barrier layer on at least one of two electrodes.…”
Section: Introductionmentioning
confidence: 99%